Numerical simulation and experimental validation of a direct current air corona discharge under atmospheric pressure - 刘兴华 何为 杨帆 王虹宇 廖瑞金 肖汉光 (Chinese physics B, 2012)
Air corona discharge is one of the critical problems associated with high-voltage equipment. Investigating the corona mechanism plays a key role in enhancing the electrical insulation performance. An improved self-consistent multi-component two-dimensional plasma hybrid model is presented for the simulation of a direct current atmospheric pressure corona discharge in air. The model is based on plasma hydrodynamic and chemical models, and includes 12 species and 26 reactions. In addition, the photoionization effect is introduced into the model. The simulation on a bar-plate electrode configuration with an inter-electrode gap of 5.0 mm is carried out. The discharge voltage- current characteristics and the current density distribution predicted by the hybrid model agree with the experimental measurements. In addition, the dynamics of volume charged species generation, discharge current waveform, current density distribution at an electrode, charge density, electron temperature, and electric field variations are investigated in detail based on the model. The results indicate that the model can contribute valuable insights into the physics of an air plasma discharge.